من مواقف ابن باديس - زغينة, محمد (الحياة, 1999)
Keywords: Réformisme – Mzab

Etude sur l'activité des oulamas dans les territoires du sud - Gardel (Section d'études des Territoires du Sud, 1938)
Keywords: Réformisme – Mzab

أعمالي في الثورة - بيوض, إبراهيم بن عمر (جمعية التراث, 1990)
Keywords: Réformisme – Mzab

الامام إبراهيم بيوض رائد الحركة الإصلاحية في الجنوب الجزائري 1339-1401هـ/1920-1981م - قرقب, عيسى (جامعة قسنطينة, 1996)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

الشيخ إبراهيم بيوض ومنهجه في الإصلاح (1899م-1981م) - سكحال, نور الدين (جامعة الامير عبد القادر للعلوم الإسلامية, 1995)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Institut al-Hayat 1925-1962 : Un exemple d'école réformiste ibadite au M'zab - Bendrissou, Salah (Université Paris 8, 1994)
Keywords: Réformisme – Mzab

Dawr al-Imām Bayyūḍ fī ‘l-Nahḍa al-Waṭaniyya al-Jazā’iriyya wa-Muqārana bi’l-ʿAllāma bin Bādīs - Qarqab, ʿĪsà (Revue d'Histoire Maghrébine, 1997)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Ibāḍiyya and orthodox reformism in modern Algeria - Shinar, Pessah (Scripta Hierosolymitana, IX, Studies in Islamic History and Civilization, 1961)
The Ibāḍī establishment in the Mzāb (98). An attempt at Sunnī-Ibāḍī reconciliation (101). Doctrinal similarities (between Reformists and Ibāḍīs) (103). The Mzābī reform movement (107). The Mzābīs and the French (108). The Ibāḍiyya and Arab nationalism (112). The enemy from within (115). On pp. 113-115 Sul. al-Bārūnī and his ideas, on the basis of his writings in the periodical al-Minhāj of Abū Isḥāq Ibr. Iṭfayyish. On pp. 115-119 the ideas of Abū Isḥāq Ibr. Iṭfayyish, on the basis of his writings in his periodical al-Minhāj).
Keywords: Bārūnī; Sulaymān al- (1870-1940); Périodiques – Egypte; Réformisme – Mzab

Islam et pensée contemporaine en Algérie: la revue al-Asâla, 1971-1981 - Deheuvels, Luc-Willy (Centre national de la recherche scientifique, 1991)
Photocopy of pp. 69, 100-101 (Ibāḍīs).* Speaking of the presence of Islamic rites and schools in the journal, Deheuvels writes of the Ibāḍīs, who counted more than 100.000 persons in Algeria in the 1970s, that their participation in al-Aṣāla has been minimal; only the Faqīh and historian Sul. b. Dāwud b. Yūsuf (see Ibn Yūsuf) has been associated regularly with the journal.
Keywords: Réformisme – Mzab

Irshād al-Ḥā’irīn - Abū ‘l-Yaqẓān, Ibrāhīm b. ʿĪsà (Maṭb. al-ʿArab, 1923)
Jundi 1965, 216 : response to opponents of a delegation to Tunisia. The author is called : Ibrāhīm b. ʿĪsà al-Qarārī.
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Enseignement – Mzab; Réformisme – Mzab

Risāla ilà al-Shaykh Bayyūḍ ʿan Humūm al-Muslimīn - Fayṣal, Shukrī (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

الدعاية إلى سبيل المؤمنين - أطفيش, إبراهيم بن محمد (المطبعة السلفية, 1923)
Keywords: Réformisme – Mzab

Un militant du réformisme et de la modernisation Ibrahim Bayyoudh - Djeghloul, Abdelkader (Eléments d'histoire culturelle algérienne, 1984)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Le réformisme ibadite en Algérie - Grossmann, Claude (Centre des hautes études sur l'Afrique et l'Asie moderne, 1971)
Keywords: Réformisme – Mzab

Le parti réformiste du M'Zab et la réforme communale - Carreau Gaschereau, Jacques (Centre des hautes études sur l'Afrique et l'Asie moderne, 1960)
Keywords: Réformisme – Mzab

Le réformisme en Algérie et dans les territoires du Sud Algérien - Soulie, Gaston Jean-Louis (Centre des hautes études sur l'Afrique et l'Asie moderne, 1941)
Keywords: Réformisme – Mzab

De Ibadiyya hun geschiedenis en leer Ibrahim Bayyud : een 20 e eeuwse Ibadi-shaykh in beschouwing genomen - Aken, Jos Van (Universiteit Utrecht, 1994)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab